YI.5 Sexual Risk Factors Amongst Women Who Have Sex with Men and Women: The Women in Indiana Sexual Health and Experience Study (WISHES). (13th July 2013) - Schick, V R; Pol, B Van Der; Dodge, B; Bell, A; Neal, C
Abstract : Background: Previous research suggests that women who have sex with women and men (WSWM) may be at a higher risk for STI than women with exclusively male (WSM) or female (WSW) partners. In contrast to previous research which has compared WSWM to WSW/WSM, the present study explored risk factors which may be unique to WSWM. Methods: Local women aged 18 or older who reported genital contact with a male and female partner within the past year were invited to participate in the study. Upon completion of an internet-based baseline survey about their sexual and STI history, participants were invited to participate in an in-person interview. During the meeting, participants engaged in a semi-structured interview followed by completion of a sexual event history calendar (SEHC). Participants were then asked to self-collect oral, vaginal and anal samples to screen for Chlamydia, Gonorrhea and Trichomoniasis. Results: Eighty participants with a mean age of 26.74 (SD = 7.97) completed the survey. The majority of the participants reported genital contact at an earlier age with a male partner (M = 16.02, SD = 3.31) than with a female partner (M = 18.93, N = 5.13).The most common type of genital contact was external genital rubbing with a male (97.5%, N = 78) and/or female (93.5%, N = 74) partner. Most participants reported a wide variety of sexual behaviours. Over half of the participants (57.5%, N = 44) reported engaging in a threesome/orgy within the past year. Data on the sequence of sexual acts was captured using the SEHC. Most participants self-collected a sample for STI screening. Approximately 30% (N = 25) of the participants reported an STI diagnosis within their lifetime and close to 10% of the participants tested positive for Chlamydia. Discussion: The study was successful in recruiting a sizable number of participants with a range of sexual experiences. The majority of participants opted to participate in all phases of the study.